Thoracic Endovascular Aortic Repair in the Ascending Aorta. Issue 5 (September 2015) - Muehle, Anja; Shah, Aamir; Khoynezhad, Ali
Abstract : Abstract: Thoracic endovascular aortic repair has become an attractive alternative treatment option for thoracic aortic disease. New devices and advanced image-guided procedures are continuously expanding the indications. This article focuses on technical aspects of transapical stent graft deployment for ascending aortic pathologies. With improving device technology, diverse available stent grafts, and imaging modalities, thoracic endovascular aortic repair has become safer and holds promising potential to expand treatment options, especially for high-risk patients requiring ascending aorta treatment.